Hyperhomocysteinemia as a Risk Factor and Potential Nutraceutical Target for Certain Pathologies - Tinelli, Caterina; Di Pino, Antonella; Ficulle, Elena; Marcelli, Serena; Feligioni, Marco (Frontiers in Nutrition, 2019)
Hyperhomocysteinemia is recognized as a risk factor for several diseases, including cardiovascular and neurological conditions. Homocysteine (HCys) is a key metabolite involved in the biosynthesis and metabolism of methionine (Met), which plays a pivotal role in the physiological cell's life cycle. The biochemistry of Met is finely regulated by several enzymes that control HCys concentration. Indeed, balanced activity among the enzymes is essential for the cell's well-being, while its malfunction could raise HCys concentration which can lead to the onset of several pathological conditions. The HCys concentration increase seems to be caused mainly by the widely diffused polymorphisms of several enzymes. Nowadays, a blood test can easily detect elevated concentrations of HCys, referred to as Hyperhomocysteinemia (HHCys). Prolonged exposure to this condition can lead to the onset of cardiovascular disease and can lead to the development of atherosclerosis, stroke, inflammatory syndromes like osteoporosis and rheumatism, as well as neuronal pathologies including Alzheimer's and Parkinson's diseases. In this review, we analyzed the literature of several pathological conditions in which the molecular pathways of HHCys are involved. Interestingly, several observations indicate that the calibrated assumption of correct doses of vitamins such as folic acid, vitamin B6, vitamin B12, and betaine may control HHCys-related conditions.